2019
DOI: 10.1007/s10439-019-02263-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of TNF-α upon Drug-Induced Toxicity in Human, Tissue-Engineered Myobundles

Abstract: A number of significant muscle diseases, such as cachexia, sarcopenia, systemic chronic inflammation, along with inflammatory myopathies share TNF-α-dominated inflammation in their pathogenesis. In addition, inflammatory episodes may increase susceptibility to drug toxicity. To assess the effect of TNF-α-induced inflammation on drug responses, we engineered 3D, human skeletal myobundles, chronically exposed them to TNF-α during maturation, and measured the combined response of TNF-α and the chemotherapeutic do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Of note, however, iDRMs require less time, cost, and expertise to generate compared to iPSC-derived myoblasts, which may be especially beneficial for generating patient-specific muscle tissues in time-sensitive or resource-limited settings. Extending culture time ( Santoso and McCain, 2021 ), integrating supporting cell types ( Juhas et al, 2018 ; Santosa et al, 2018 ; Santoso and McCain, 2021 ), providing electrical ( Nedachi et al, 2008 ; Chen et al, 2021 ) or mechanical stimulation ( Heher et al, 2015 ; Chang et al, 2016 ), or engineering 3-D tissues ( Madden et al, 2015 ; Uzel et al, 2016 ; Costantini et al, 2017 ; Davis et al, 2019 ; Ariyasinghe et al, 2020 ; Ebrahimi et al, 2021 ) or earlier exposure to AO could also help induce muscle maturation and proper localization of dystrophin and α-actinin.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, however, iDRMs require less time, cost, and expertise to generate compared to iPSC-derived myoblasts, which may be especially beneficial for generating patient-specific muscle tissues in time-sensitive or resource-limited settings. Extending culture time ( Santoso and McCain, 2021 ), integrating supporting cell types ( Juhas et al, 2018 ; Santosa et al, 2018 ; Santoso and McCain, 2021 ), providing electrical ( Nedachi et al, 2008 ; Chen et al, 2021 ) or mechanical stimulation ( Heher et al, 2015 ; Chang et al, 2016 ), or engineering 3-D tissues ( Madden et al, 2015 ; Uzel et al, 2016 ; Costantini et al, 2017 ; Davis et al, 2019 ; Ariyasinghe et al, 2020 ; Ebrahimi et al, 2021 ) or earlier exposure to AO could also help induce muscle maturation and proper localization of dystrophin and α-actinin.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased capillary density is associated with poor prognoses of cachexia and is influenced by TNFα [ 167 ]. TNFα was also shown to inhibit myofiber maturation in tissue-engineered myobundles [ 168 ].…”
Section: In Vitro Modeling Of Cachexiamentioning
confidence: 99%
“…Over the past two decades, approaches for engineering 3D muscle bundles have been advanced and refined. Several different types of culture chambers with anchor points have been fabricated ( Costantini et al, 2017a ; Smith et al, 2016 ), including Velcro and nylon frames ( Davis et al, 2017 , 2019 ; Madden et al, 2015 ; Rao et al, 2018 ; Smith et al, 2016 ; Zhang et al, 2018 ) and microfabricated chambers with pillars ( Osaki et al, 2018 , 2020 ; Uzel et al, 2016 ). Testing of multiple ECM solutions has also revealed that fibrin hydrogels are optimal for encapsulating myotubes due to their strength ( Hinds et al, 2011 ; Pollot et al, 2018 ), although these hydrogel compositions are not necessarily physiological.…”
Section: Engineered In Vitro Models Of Neuromusculmentioning
confidence: 99%
“…Testing of multiple ECM solutions has also revealed that fibrin hydrogels are optimal for encapsulating myotubes due to their strength ( Hinds et al, 2011 ; Pollot et al, 2018 ), although these hydrogel compositions are not necessarily physiological. To improve assay capabilities, contractile forces have been measured in 3D muscle bundles with custom force transducers ( Davis et al, 2019 ; Madden et al, 2015 ; Rao et al, 2018 ) or by tracking the displacement of pillars ( Osaki et al, 2018 ; Uzel et al, 2016 ). Similar to 2D tissues, biophysical cues, such as mechanical stretch ( Powell et al, 2002 ) and optogenetic stimulation ( Mills et al, 2019 ), or addition of fibroblasts ( Dennis et al, 2001 ) have also been shown to mature 3D muscle bundles.…”
Section: Engineered In Vitro Models Of Neuromusculmentioning
confidence: 99%